The Role of Rural Production Systems in the Transformation of Rural Areas in Kediri Regency - Gustia Kusumastuti (The Indonesian Journal of Planning and Development, 2023)
Rural transformation involves comprehensive changes at the community level, including shifts from agriculture to non-agricultural sectors, infrastructure development, and socio-cultural transitions toward urbanization. The organization of rural production serves both as a driver and a reflection of these transformative processes. Kediri Regency in East Java is currently undergoing such changes, with 29 villages reclassified as urban between 2000 and 2010. While a shift toward non-agricultural sectors is evident, the agricultural sector in several areas remains vibrant and adaptive. This study analyzes rural production systems in the context of this transformation, focusing on three villages with varying proximity to Kediri City (a primary city) and Pare (a secondary city). Employing a quantitative method and descriptive statistical analysis, the study finds that rural production systems play a vital role in maintaining the relevance of agriculture during transformation. Significant progress is observed in physical assets, natural resource utilization, and social capital—manifested through increased use of modern tools, crop diversification, and strengthened social networks. Local production systems are gradually modernizing, with improved coordination and emerging innovation, even though collective farming practices remain prevalent. Productivity, income generation, and market linkages are improving, especially in villages located closer to urban centers. These areas display faster adaptation due to spatial advantages and more robust asset portfolios. The findings highlight the need to include rural production systems in rural development strategies to foster agricultural innovation, expand market and institutional linkages, and reinforce social and economic resilience in the face of transformation.